2003
DOI: 10.1016/s0741-5214(03)00085-5
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of intact thoracoabdominal aortic aneurysms in the United States: Hospital and surgeon volume-related outcomes

Abstract: Greater hospital and surgeon TAAA treatment volumes contribute to better outcome. Given the relative high perioperative mortality associated with TAAA repair, regionalization of care to high-volume providers with consistently lower postoperative mortality deserves consideration by patients, physicians, and health care planners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
237
4
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 362 publications
(256 citation statements)
references
References 18 publications
8
237
4
7
Order By: Relevance
“…Indeed, adequate staff support and hospital and surgeon volume significantly influence postoperative survival. Another study 234 clearly demonstrated that less experience correlated with increased post-operative mortality: in 1,542 operated patients, a significant difference (p < .001) in mortality was determined between low volume hospitals (27.4%) and high volume hospitals (15%). Also, low volume surgeons had significantly (p < .001) higher mortality rates (25.6%) compared with high volume surgeons (11.0%).…”
Section: Managementmentioning
confidence: 96%
“…Indeed, adequate staff support and hospital and surgeon volume significantly influence postoperative survival. Another study 234 clearly demonstrated that less experience correlated with increased post-operative mortality: in 1,542 operated patients, a significant difference (p < .001) in mortality was determined between low volume hospitals (27.4%) and high volume hospitals (15%). Also, low volume surgeons had significantly (p < .001) higher mortality rates (25.6%) compared with high volume surgeons (11.0%).…”
Section: Managementmentioning
confidence: 96%
“…Importantly, a recent study of surgical repair of thoracoabdominal aortic aneurysms found that surgical mortality was substantially higher in lowvolume hospitals and for low-volume surgeons compared with high-volume hospitals and high-volume surgeons. 28 An alternative approach for the repair of descending thoracic aneurysms is the use of a transluminally placed endovascular stent-graft ( Figure 10). This technique has the advantage of being far less invasive than surgery, with potentially fewer postoperative complications and lower morbidity.…”
Section: Descending Thoracic Aortic Aneurysmsmentioning
confidence: 99%
“…Morbidity and mortality rates vary according to the extent of the disease and the expertise of the surgeon. 3 Statewide audits provide a sobering picture of overall results, with 30-day mortality approaching 20%. 4 Minimally-invasive endovascular repair of TAAA has the potential to reduce mortality and morbidity.…”
Section: ¤ ¤mentioning
confidence: 99%